2003
DOI: 10.1590/s1516-89132003000200016
|View full text |Cite
|
Sign up to set email alerts
|

Growth and photosynthetic capacity in two woody species of cerrado vegetation under different radiation availability

Abstract: Seedlings of two woody species of cerrado vegetation, Copaifera langsdorffii and Eriotheca gracilipes, were studied under three different radiation availability (100, 80 and 30% transmittance). Full solar radiation brought about more biomass, higher total leaf area, higher maximal photosynthesis per crown on area or on mass bases and higher photosynthetic capacity on area bases. Only the photosynthetic capacity values on leaf mass bases were higher in both species under low radiation availability (80 and 30% t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 16 publications
2
7
0
1
Order By: Relevance
“…Whereas Chaetocarpus echinocarpus, which is a typical understory species (shady environments) from seasonal semideciduous and riparian forests of eastern Mato Grosso 2002) Ronquim et al (2003) observed that Eriotheca gracilipes needs high solar radiation levels for growth (100% transmittance), under which it exhibits higher photosynthetic capacity and higher biomass accumulation. According to these authors, under shaded conditions (30% transmittance) E. gracilipes does not produce enough resources to sustain the demand required for the formation of reproductive structures.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas Chaetocarpus echinocarpus, which is a typical understory species (shady environments) from seasonal semideciduous and riparian forests of eastern Mato Grosso 2002) Ronquim et al (2003) observed that Eriotheca gracilipes needs high solar radiation levels for growth (100% transmittance), under which it exhibits higher photosynthetic capacity and higher biomass accumulation. According to these authors, under shaded conditions (30% transmittance) E. gracilipes does not produce enough resources to sustain the demand required for the formation of reproductive structures.…”
Section: Resultsmentioning
confidence: 99%
“…As a compensatory mechanism, plants can change their leaf morphology and anatomy (CASTRo et al, 2005), as well as the chloroplast structure and position, chlorophyll content, and export and distribution of leaf assimilates (dWELLE, 1985). in general, plants rely on mechanisms that protect against impaired photosynthesis owing to energy reduction resulting from the restriction of incident solar radiation (RonqUim et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Gallery forests, semideciduous forests, and palm swamp co-occur with Brazilian neo-tropical savannas that show different physiognomies (Ratter et al, 2003). There are many environmental factors such as distrophic soils (Haridasan, 2008) and contrasting irradiance patterns (Nardoto et al, 1998;Kanegae et al, 2000) that impose adjustments to Cerrado plants during their life cycle, especially in young plants growing under contrasting irradiance (Ronquim et al, 2003;Prado et al, 2006). Distinct light regimes in each cerrado physiognomy may promote the establishment of different species assemblage or functional types.…”
Section: Introductionmentioning
confidence: 99%